Juridical Analysis of Portrait Publication Without The Permission of The Creator because of Law Number 28 of 2014 Concerning Copyright - Muhammad Al Habsy Ahmad (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This Research aimed to determine how I protect the law against the victim of I-portrait publication without the permission of the Author I reviewed I of Law No. Ihak Icopy. The research method used in this Research is the type of normative juridical Research. The results of this study showed that: There are two types of protection, preventive and repressive protection. Preventive protection is aimed at preventing copyright infringement on photography. Repressive protection is aimed at resolving copyright infringements on portraits. Meanwhile, attempts at settlement in the event of a dispute between the Photographer and the person being photographed can be carried out in two ways: by filing a lawsuit against I-Commerce Court or arbitration. Submission of a case in the Commercial Court is carried out if the Photographer does not ask for permission in advance from the person who becomes the object of the portrait. As for the suggestions that the Author gives in this matter, they are: (1) the government must provide strict sanctions to the copyright violators of the photographs of those who use the pictures of other persons for promotion, because of the preventive protection of copyrights for portraits, photographers rarely do this in publishing the results of their works. His portrait. (2) Photographers are advised to only use or publish the portraits of other people for promotion easily after getting the approval of them or their heirs. (3) The government should provide socialization to the public that photographers use their portraits or their portraits for commercial performances that have received the protection of those regulated by them in Law No. 128 of 12014 on copyright.